(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1858)
Joseph Robertson presents his argument that wine was a common drink in Scotland. As evidence, he quotes legislation from the seventeenth century prohibiting the sale and consumption of wine in the Western Isles.